Effect of unilateral training and bilateral training on physical performance: A meta-analysis - Zhang, Wenfeng; Chen, Xing; Xu, Kun; Xie, Hezhi; Li, Duanying; Ding, Shicong; Sun, Jian (Frontiers in Physiology, 2023)
Background In Unilateral (UNI) exercises are more effective than bilateral (BI) exercises in improving athletic performance is debatable. Objectives this meta-analysis investigated the effects of UNI and BI exercises on different effect indicators of jump ability, sprint ability, maximal force, change of direction ability, and balance ability. Data Sources PubMed, Google Scholar, Web of science, CNKI, Proquest, Wan Fang Data. Study Eligibility Criteria To be eligible for inclusion in the meta-analysis, the study had to be: (1) athletes; (2) UNI training and BI training; (3) the intervention period had to be more than 6 weeks and the intervention frequency had to be more than 2 times/week; (4) the outcome indicators were jumping ability, sprinting ability, maximum strength, and change of direction and balance. Study Appraisal and Synthesis Method We used the random-effects model for meta-analyses. Effect sizes (standardized mean difference), calculated from measures of horizontally oriented performance, were represented by the standardized mean difference and presented alongside 95% confidence intervals (CI). Results A total of 28 papers met the inclusion criteria, and Meta-analysis showed that UNI training was more effective than BI training in improving jumping ability (ES=0.61,0.23 to 0.09; Z=3.12, P=0.002<0.01), sprinting ability(ES=-0.02, -0.03 to -0.01; Z=2.73, P=0.006 < 0.01), maximum strength(ES=8.95,2.30 to 15.61; Z=2.64, P=0.008 > 0.05), change of direction ability (ES=-0.03, -0.06 to 0.00; Z=1.90, P=0.06 ＞ 0.01) and balance ability (ES=1.41,-0.62 to 3.44; Z=1.36, P=0.17 ＞ 0.01). The results of the analysis of moderating variables showed that intervention period, intervention frequency and intervention types all had different indicators of effect on exercise performance. Conclusions: UNI training has a more significant effect on jumping and strength quality for unilateral power patterns, and BI training has a more significant effect on jumping and strength quality for bilateral power patterns.